2019
DOI: 10.1002/qua.25963
|View full text |Cite
|
Sign up to set email alerts
|

Promising sensitizers for dye sensitized solar cells: A comparison of Ru(II) with other earth's scarce and abundant metal polypyridine complexes

Abstract: There has recently been a growing interest in dye sensitized solar cells (DSSCs) based on ruthenium metal, but due to the scarcity and high price of ruthenium, design of better and cheaper light adsorbent dyes based on more abundant metal ions is one of the key issues for future development of the DSSCs. Using density functional theory (DFT) and time‐dependent DFT we have studied the properties of new and abundant metal ion‐based polypyridyl dyes for p‐type DSSCs and compared with ruthenium and other scarce me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 96 publications
1
32
0
Order By: Relevance
“…Other articles concerning the push-pull strategy in designing metal-free DSSC dyes include, but are not limited to, Refs. [116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134].…”
Section: Organic Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…Other articles concerning the push-pull strategy in designing metal-free DSSC dyes include, but are not limited to, Refs. [116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134].…”
Section: Organic Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…a hydrogen evolution catalyst, instead to a redox agent, such as I − 3 /I − . 11,13,16,18 Furthermore, apart from just addressing the properties of the DSSCs, hole conducting organic polymers have been put forward as viable alternatives to NiO or other metal oxide materials, as the tuning of the physicochemical properties of polymers is easier 19 than those of NiO.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of the chemical structure of the sensitizers on the photovoltaic properties were investigated. [ 16–19 ] For example, polypyridyl dyes based on Cr 2+ and V 3+ show better performance in comparison with ruthenium‐ and other scarce metal‐based polypyridyl dyes due to the moderate LHE and high efficiencies of electron and hole injection, which make them promising alternatives to scarce Ru 2+ metal ion. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] For example, polypyridyl dyes based on Cr 2+ and V 3+ show better performance in comparison with ruthenium-and other scarce metal-based polypyridyl dyes due to the moderate LHE and high efficiencies of electron and hole injection, which make them promising alternatives to scarce Ru 2+ metal ion. [17] In addition, theoretical insights into the effect of polycyclic aromatic hydrocarbons (PAHs) on monascus pigments (MPs) and as a photosensitizer for solar cells showed that the presence of the PAHs reduces the electronic band gap and the electron injection efficiency of MPS. [18] The absorption peaks of the MPs-fluorene, MPs-naphthalene, and MPs-anthracene also appear in the visible region.…”
mentioning
confidence: 99%